1997
DOI: 10.1046/j.1365-3083.1997.d01-438.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating T Cells of Patients with Active Psoriasis Respond to Streptococcal M‐Peptides Sharing Sequences with Human Epidermal Keratins

Abstract: Psoriasis is a T-cell mediated inflammatory skin disease which has been associated with group A, bhaemolytic streptococcal infections. Four 20 a.a. long M6-peptides sharing 5-6 a.a. sequences with human epidermal keratins were identified. To investigate the role of potentially cross-reactive T cells in the pathogenesis of psoriasis, interferon-g (IFN-g) and interleukin-4 (IL-4) responses of circulating T cells to these peptides were analysed by ELISPOT and RT-PCR in 14 psoriatic patients, 12 healthy individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 69 publications
3
56
0
2
Order By: Relevance
“…Keratinocyte-derived proteins [18][19][20][21][22]42 , among which keratins, were previously identified as autoantigens, especially in a subset of patients with psoriasis linked to group-A b-hemolytic streptococcal throat infections. Our study now identifies the AMP LL37 as a new autoantigen in psoriasis that is recognized by circulating T cells in 46% of psoriasis patients and up to 75% of patients with moderate-to-severe psoriasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Keratinocyte-derived proteins [18][19][20][21][22]42 , among which keratins, were previously identified as autoantigens, especially in a subset of patients with psoriasis linked to group-A b-hemolytic streptococcal throat infections. Our study now identifies the AMP LL37 as a new autoantigen in psoriasis that is recognized by circulating T cells in 46% of psoriasis patients and up to 75% of patients with moderate-to-severe psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…We also tested reactivity to keratins, as these proteins were identified as autoantigens in a subset of psoriasis patients [18][19][20][21][22] . In keeping with the literature [18][19][20][21][22] , we detected reactivity to Keratins that was statistically significant for Keratin17 ( Supplementary Fig. 3, lefts panels).…”
Section: Ll37 Frequently Induces Proliferation Of Psoriatic T Cells mentioning
confidence: 99%
“…The concept of molecular mimicry explains how anti-streptococcal T cells can be activated in the skin to target-specific tissue antigen(s) and subsequently causing disease. 20,21 Indeed, peripheral blood T cells from psoriatic patients but not healthy controls have been shown to respond to several synthetic peptides corresponding to these shared homologous sequence motifs for the production of IFN-c. 22,23 Further study demonstrated that CD8 1 T cells in the peripheral blood from psoriasis patients carrying the HLA-Cw6 allele, which has been reported to have a strong association with psoriasis, had a significant IFN-c response to the peptide selected from the shared sequence by keratin 17 and M6 protein and the predicted HLA-Cw6 binding. 24 Additionally, the majority (.90%) of these responding cells express the skin homing cutaneous lymphocyteassociated antigen determinant.…”
Section: What Causes the Activation Of Pathogenic T Cells In Psoriasis?mentioning
confidence: 97%
“…Another approach has been to try to identify specific antigens (both exogenous and endogenous) in patients with psoriasis that could activate the immune system with creation of pathogenic T cells. Both infectious and noninfectious T-cell activating factors have been suggested as candidate triggering factors, including retrovirus (human immunodeficiency virus 1 35 ), bacteria-derived superantigens, 36 gous keratin-derived peptides, 38 neuropeptides such as substance P, 39 and human papillomavirus. 40 Thus far we have focused on acquired-type of immune response (Figures 2 and 3 …”
Section: A Dynamic Immunologic Model In Which 3 Different Immunocytesmentioning
confidence: 99%